Pushing to the low limits: tetraazaanthracenes with very low-lying LUMO levels and near-infrared absorption. Issue 73 (1st September 2017) - Gampe, Dominique Mario; Schramm, Stefan; Nöller, Florian; Weiß, Dieter; Görls, Helmar; Naumov, Panče; Beckert, Rainer
Abstract : Here we explain the extensive changes which result by transforming benzothiadiazoles to highly electron-deficient tetraazaanthracenes. Abstract : Here we propose the combination of the 4-alkoxythiazole donor motif with highly photostable tetraazaanthracenes as electron-acceptor units. The segregated frontier orbitals in these dyes afford optical band gaps of 1.4–1.1 eV. Cyclic voltammetry confirmed the very low-lying LUMO levels that are attributed to the highly electron-deficient tetraazaanthracene moiety.